Metafisica dello spazio.: L’icona, Pavel Florenskij e l’empirismo trascendentale - Colombo, Andrea (Scenari, 2021)
This paper attempts to explain the unified philosophical, mathematical, and religious elements of Pavel Florenskij’s aesthetic theory. Previously understood as removed from contemporary developments in philosophy, Florenskij’s concept of the Icon reveals instead how connected his thought is to other 20th century thinkers concerned with the development of science and new ontology such as Gilles Deleuze, Simondon, and Bergson.